Effects of Adding Red Dragon Fruit Peel (Hylocereus polyrhizus) at Different Dosages in Feed on the Color Change of Clownfish (Amphiprion percula) - Yesepus Arianto Otu; Felix Rebhung; Wesly Pasaribu (Grouper, 2024)
Karotenoid, a pigment responsible for yellow, orange, and red hues, was explored in this study to ascertain its impact on enhancing the coloration of clownfish (Amphiprion percula) by incorporating red dragon fruit rind (Hylocereus undatus) flour into their feed. The research involved four distinct treatments: (a) FF999 commercial feed without red dragon fruit rind flour addition, (b) 10% red dragon fruit rind flour + 90% FF999 pellets, (c) 15% red dragon fruit rind flour + 85% FF999 pellets, and (d) 20% red dragon fruit rind flour + 80% FF999 pellets. Evaluation parameters included color measurements using RGB values, transformed into HSB values. The method used is a Completely Randomized Design (CRD), the final HSB color quality data is tabulated using the Excel application and analyzed descriptively. Results revealed that the inclusion of red dragon fruit rind flour induced changes in the Hue, Saturation, and Brightness (HSB) values, effectively maintaining the clownfish's color akin to their natural hue (A. percula) during cultivation.